Dampak Kesenjangan Gender Terhadap Kesehatan Perempuan: Tinjauan Hukum Dan Kebijakan Kesehatan - Zacky Alamsyah Bustami; Radit Febri Kurniawan (CV. ITTC INDONESIA, 2024)
Gender inequality in Indonesia is a complex issue that significantly impacts women's health. This study aims to analyze the effects of gender inequality on access to healthcare services, reproductive health, and women's mental health. Despite the existence of legal frameworks and policies supporting the protection of women's rights, challenges in their implementation remain substantial. The Family Planning (KB) program has shown success in reducing birth rates in several regions; however, there are still barriers related to access to information and education about contraception, particularly for young women. The success of health policies is evident in the increased access to basic health services for women, yet social stigma surrounding reproductive health and gender-based violence continues to pose significant challenges. Additionally, the lack of adequate resources and healthcare infrastructure in remote areas hampers policy implementation. Community involvement in policy formulation is crucial to ensure that these policies reflect local needs. This research emphasizes the necessity for collaborative efforts between the government, civil society, and international organizations to raise awareness about the importance of gender equality in health and to strengthen the enforcement of laws protecting women and children.